NILAI-NILAI KONSELING KELUARGA DALAM KITAB UQUDULUJJAIN KARYA SYAIKH NAWAWI AL BANTANI - Unsiatul Muthi’ah; Abdul Mughni; Saifullah (Fakultas Dakwah Universitas Ibrahimy, 2020)
Value is something that is believed to be true, trusted and felt useful, and is manifested in its attitude or behavior. Family counseling is an effort to provide assistance to individual family members through improving family communication so that the potential to develop is as optimal as possible and the problem can be overcome on the basis of the willingness to help from all family members based on their willingness and love for the family. This researcher uses the literature study research method. The results of the study concluded that the opinion of Shaykh Nawawi Al Bantani on book of Uqudulujjain Fi Bayani Huquqizzaujain about sakinah households, he believes there are four articles in it, namely; the right of the husband to the wife, the right of the wife to the husband, forbidden for women to pray outside the house, and forbidden to see other than muhrim